Power, Optimism and Risk-taking in the case of Mongolia - Khishignyam, Bazarvaani; Bumdari, Dagva-Ochir; Badamdash, Dashdavaa (Politologia, 2023)
This research aimed to analyze the correlation between the sense of power, optimism, and the proclivity for risk-taking, using the research method described by Anderson and Galinsky in their article “Power, optimism, and risk-taking” in 2006. This research examines power within interpersonal communications by analysing the correlation of power, the behavioural approach/inhibition, optimism, and the inclination for risk-taking, using methods of interview, experiment, and testing. The research was conducted in 4 sequential studies. Study I examined the concept of power consciously and examined its effect upon the tendency in motivation through the behavioral approach and inhibition system. Study II examined the concept of power unconciously, and measured its effect in risk-taking tendencies through the gain/loss frame. Study III focused on the correlation between a general sense of power and an optimistic attitude. Study IV specifically selected persons in supervisory positions in both the private and public sectors, assuming them to be practicing positions of relative power and control; and then measured their tendencies in risk-taking through the gain/loss frame and the behavioral approach and inhibition system. Finally, we attempted to make basic comparisons of our findings with similar findings in the cases of the USA, China and Japan. Although we proposed a similar hypothesis as Anderson and Galinsky, our research findings revealed that results of Mongolian participants strongly contrasted with theirs. While recognizing our limitations in customizing this research methodology to our local context, we may have to consider other contextual factors such as the feeling of freedom inherent in a nomadic culture, overwhelmingly unstable mid-level managerial positions (both in Government and the private sector), the heavy responsibility and limitations imposed upon those in supervisory positions, and last but not least, that our sample of participants were mostly between 18-40 years of age and brimming with optimism and self-efficacy.